SAE Technical Paper Series 2017
DOI: 10.4271/2017-01-1258
|View full text |Cite
|
Sign up to set email alerts
|

Extended Range Electric Vehicle Powertrain Simulation, and Comparison with Consideration of Fuel Cell and Metal-Air Battery

Abstract: I hereby declare that I am the sole author of this thesis. This is a true copy of the thesis, including any required final revisions, as accepted by my examiners. I understand that my thesis may be made electronically available to the public.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In addition, the high battery price meant that the savings in EV TCO value were insignificant. Several similar studies in Thailand [24] have also shown a similar case in battery replacement costs because of the absence of regulations regarding battery recycling efficiency and the minimum number of business actors engaged in this field [46].…”
Section: Sensitivity Analysismentioning
confidence: 92%
“…In addition, the high battery price meant that the savings in EV TCO value were insignificant. Several similar studies in Thailand [24] have also shown a similar case in battery replacement costs because of the absence of regulations regarding battery recycling efficiency and the minimum number of business actors engaged in this field [46].…”
Section: Sensitivity Analysismentioning
confidence: 92%
“…Furthermore, they have a high energy efficiency and a long lifespan [67]. In comparison to gasoline engines, the Zn-air range extender has lower tailpipe emissions [69]. However, there are some problems that need to be addressed before Zn-air can be used commercially in EVs.…”
Section: Zinc-air Battery As a Range Extender 61 Definitions Mechanis...mentioning
confidence: 99%
“…The authors claimed that the potential is greater when combining a Zn-air battery with a Li-ion battery in a dual battery configuration. Catton et al [69] modeled and compared various powertrains including an REEV with Zn-air, a conventional gasoline powered vehicle, a fuel cell vehicle, and an REEV with ICE. The comparison criteria included energy consumption, range, life cycle and tailpipe emissions, cost, and consumer acceptance.…”
Section: Recent Research Developmentsmentioning
confidence: 99%